Proselytism and the Right to Freedom from Improper Irreligious Influence: The Example of Public School Education - De Freitas, SA (Potchefstroom Electronic Law Journal, 2017)
Jurisprudentially speaking, "proselytism" is a concept within the larger genus of the protection of religious rights and freedoms. The word lends itself to differing opinions. However, there is a popular school of thought that "proselytism" has to do only with influencing people to adopt a particular religion. Such an understanding relies on the view that only the "religious" can be insidious and bear the potential to improperly proselytise, and thus excludes the possibility of improper irreligious forms of influence. In referring to the example of public-school education, it is argued that as much as the religious has the potential for improper proselytising, irreligious teachings or expressions also run the risk of improper proselytising. Not only are irreligious beliefs in many instances diametrically opposed to religious beliefs; they are a belief in themselves and cannot be seen as necessarily harmless or without the potential to proselytise improperly. Consequently, this article introduces an equitable and accommodative understanding of proselytism, which places the potentially harmful effects of both religious and irreligious beliefs on an equal footing with each other (something befitting to plural and democratic paradigms). This article therefore also cultivates further debate on improper irreligious proselytism in religious rights and freedoms jurisprudence, a scant topic in human rights jurisprudence.